2003
DOI: 10.1016/s1059-1311(02)00256-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of probable relationship between Toxoplasma gondii and cryptogenic epilepsy

Abstract: There might be a causal relationship between chronic toxoplasmosis and the aetiology of cryptogenic epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 10 publications
2
37
1
3
Order By: Relevance
“…Exposure to O. volvulus, T. canis and T. gondii was associated with an increased prevalence of epilepsy in other case-control studies [8], [9], [10], [11], [12], [13], [28], [29], [30]. Previous studies reporting the association between parasitic infection and epilepsy have used seropositivity to define exposure[8], [9], [14], [28], [29], [31], [32], [33], with none taking into account the degree of exposure as a predictor for risk of ACE.…”
Section: Discussionmentioning
confidence: 78%
“…Exposure to O. volvulus, T. canis and T. gondii was associated with an increased prevalence of epilepsy in other case-control studies [8], [9], [10], [11], [12], [13], [28], [29], [30]. Previous studies reporting the association between parasitic infection and epilepsy have used seropositivity to define exposure[8], [9], [14], [28], [29], [31], [32], [33], with none taking into account the degree of exposure as a predictor for risk of ACE.…”
Section: Discussionmentioning
confidence: 78%
“…7 The prevalence of Fasciolosis was 3% in Portugal, 7% in Egypt and 9% in Peru. The highest prevalence was found in Bolivia, where stool examination revealed a prevalence of 72%, and serologic tests were positive in 100%.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies investigated the association between T. gondii infection and epilepsy (Akyol et al, 2007[1]; Allahdin et al, 2015[2]; El-Tantawy et al, 2013[11]; Eraky et al, 2016[12]; Ngugi et al, 2013[23]; Stommel et al, 2001[28]; Yazar et al, 2003[34]; Zibaei et al, 2011[35]). Some of these studies found significant association between epilepsy and Toxoplasma infection and some did not (Ngoungou et al, 2015[22]).…”
Section: Discussionmentioning
confidence: 99%
“…Risk of epilepsy in people with toxoplasmosis has also been discussed by many researchers (Akyol et al, 2007[1]; Ngugi et al, 2013[23]; Palmer, 2007[24]; Yazar et al, 2003[34]). However, due to lack of well-matched case-control studies in large enough population of epileptic patients, there is not yet a consensus on association between epilepsy and latent Toxoplasma infection (Ngoungou et al, 2015[22]).…”
Section: Introductionmentioning
confidence: 99%